مظاهر الاغتراب في رواية الملحد لـ "عبد الرشيد هميسي" - منصر, يمينة; بن عمر, سهام; سالمي, هاجر (جامعة الوادي - University of Eloued, 2023)
الاغتراب ظاهرة إنسانية شملت مختلف أنماط الحياة، وهي قديمة مرتبطة بظهور الإنسان، وجديدة من حيث الدراسات الأدبية، كونها مرتبطة بأزمات الإنسان المعاصر. نسعى في دراستنا التي هي بعنوان مظاهر الاغتراب في رواية الملحد لعبد الرشيد هميسي، تطرقنا فيها إلى البحث عن تجليات و مظاهر الاغتراب في رواية الملحد ؟ متبعين خطة متكونة من مدخل بعنوان ماهية الاغتراب ومظاهره وتجلياته في الأدب، و فصلين أولهما : مظاهر الاغتراب في رواية الملحد و فصل ثان: تجليات الاغتراب من خلال المكونات السردية في رواية الملحد. اعتمدنا على منهجين سياقيين هما النفسي والاجتماعي في تحليل ظاهرة الاغتراب كما استحضرنا بعض آليات المنهج السيميائي في تحليل العتبات النصية، كما استدعى المنهج البنيوي في دراسات البنيات السردية (بنية الزمان، بنية المكان) معا الاعتماد على آليتي الوصف والتحليل. وللإنجاز الدراسة استعنا بمراجع قيمة نذكر منها : الاغتراب دراسة تحليلية لشخصيات الطاهر بن جلول الروائية، ليحي العبد الله. دراسات في سيكولوجية الاغتراب لعبد اللطيف محمد خليفة. الاغتراب في الثقافة العربية لحليم بركات. ومن أهم النتائج المتحصل عليها الاغتراب، ظاهرة فرضت نفسها في العمل الإبداعي الأدبي شعرا وسردا، طغيان الاغتراب الاجتماعي و بدرجة أقل النفسي والديني، ثم الفكري والاغتراب الثقافي والعاطفي. Alienation is a human phenomenon that includes various lifestyles. It is old and linked to the emergence of man, and new in terms of literary studies, being linked to the crises of contemporary man. In our study, which is entitled Manifestations of Alienation in the Atheist Novel by Abd al-Rashid Hamisi, we seek to search for manifestations and manifestations of alienation in the Atheist Novel? Following a plan consisting of an introduction entitled What is alienation and its manifestations and manifestations in literature, and two chapters, the first of which is: manifestations of alienation in the novel of the atheist and the second chapter: manifestations of alienation through the narrative components in the novel of the atheist. We relied on two contextual approaches, the psychological and the social, in analyzing the phenomenon of alienation. We also evoked some of the mechanisms of the semiotic approach in analyzing textual thresholds. The structural approach in studies of narrative structures (the structure of time, the structure of place) together called for reliance on the two mechanisms of description and analysis. To complete the study, we used valuable references, among which we mention: Alienation is an analytical study of the characters of Al-Taher Bin Jalul, the novelist, by Yahya Al-Abdullah. Studies in the psychology of alienation by Abdul Latif Mohammed Khalifa. Alienation in Arab Culture by Halim Barakat. Among the most important results obtained is alienation, a phenomenon that imposed itself in the literary creative work in poetry and narration, the tyranny of social alienation and to a lesser degree psychological and religious, then intellectual and cultural and emotional alienation
أدب حديث ومعاصر
Keywords: الاغتراب - رواية الملحد – السرد; alienation - the atheist's novel - narration